Home Surveillance with Encrypted Video Data - Siti Nur Aisyah Abdul Hei; Mohd Yusof, Mohd Azahari (Applied Information Technology And Computer Science, 2023)
Home surveillance with encrypted video data focuses on helping to solve the problems of people’s insecurity about their home security when leaving it for a long time. The open-source mobile application and unprotected video data was also a problem that needed to be solved. This report proposed home surveillance which will be implemented with movement detection sensors with Closed-circuit Television (CCTV). Subsequently, developing a secure application system that comes with notification features to control the problem is discussed in this report. The method used is on a house prototype by combining the sensors and connection with application which has several security elements. The report was expected to have a good result and achieve the objectives for both the sensors and the application’s security features in terms of its efficiency. Along with the Internet of Things (IoT), the home surveillance system functions worked as expected and the user can receive real-time situation notifications about their house.